Pengaruh Cashless Lifestyle, Perceived Ease of Use, dan Environmental Awareness terhadap Minat Menggunakan E-Wallet pada Mahasiswa Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Hikmatus Sholihah; Mohammad Mirza Pratama (Lembaga Yasin AlSys, 2026)
The development of digital technology has transformed society’s payment system from cash transactions to e-wallet-based non-cash transactions that offer convenience, speed, and efficiency. This phenomenon also occurs among students, including at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, which has supported the implementation of digital payment systems through various technology-based services. This study aims to analyze the effects of cashless lifestyle, perceived ease of use, and environmental awareness on the intention to use e-wallets among students at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, both partially and simultaneously. This study used a quantitative approach with an associative research design. The research population consisted of all active undergraduate students, while the sample comprised 388 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through a Likert-scale questionnaire distributed online using Google Forms, then analyzed through instrument testing, classical assumption testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results showed that cashless lifestyle, perceived ease of use, and environmental awareness each had a positive and significant effect on the intention to use e-wallets. Simultaneously, the three variables also had a positive and significant effect on the intention to use e-wallets among students at Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember. The conclusion of this study affirms that increasing cashless lifestyle, perceived ease of use, and environmental awareness can encourage students’ intention to use e-wallets as a means of digital transactions. The implications of this study provide practical contributions to the development of digital payment services in higher education environments and serve as input for e-wallet service providers in designing usage strategies that are easier, more efficient, and oriented toward environmental awareness.